Proven Technologies for Doubling Cotton Production in India and Enhancing Quality of Lint and Seed - Narayanan, S. S.; Singh, Phundan; Ravindranath, K. (International Journal of Economic Plants, 2017)
India is no less inferior to many advanced countries in R&D achievements under public sector, private sector seed industry and also the technological and textile institutions all over the country. If the realistic evaluation is made, except for improved cultivars, the farmers’ adoption rate of the recommended technologies for planting, production and processing have been awfully low, poor and inadequate, given the wide diversity of Indian cotton farming conditions. Hardly 15−20% of the cotton growers have adopted the wholesome technology. The urgent need is to organize the national cotton farming on a highly scientific and technology-oriented. India can achieve its goals on highest yield and high quality of cotton lint and cottonseeds and their effective utilization.